Reason and the Lover - Fleming, John V. (Book collections on Project MUSE., 1984)
This textual and intertextual analysis of the dialogue in Jean de Meun's Roman de la Rose combines specific close readings of texts with a rich theoretical argument to establish Reason's moral primacy in the poem's economy. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.